Phenolic Profile and Bioactivities of Sideritis perfoliata L.: The Plant, Its Most Active Extract, and Its Broad Biological Properties - Sarikurkcu, Cengiz; Locatelli, Marcello; Mocan, Andrei; Zengin, Gokhan; Kirkan, Bulent (Frontiers in Pharmacology, 2020)
Sideritis, also named “ironwort”, “mountain tea” or “shepherd's tea”, is a genus of flowering plants known as herbal medicine in Mediterranean area traditional medicine systems, and generally consumed as a herbal tea. Its use as a herbal tea, and traditional herbal medicine is quite popular. Currently, in literature are present only few papers on Sideritis perfoliata L., and only one reports the liquid chromatography coupled to diode array detection and electrospray ionization tandem mass spectrometry (LC-DAD-ESI-MSn) profile and content of phenolic compounds without considering a possible correlation with its biological activities. The herein reported paper aims to investigate the antioxidant activities by means of several different biological/biochemical assays (radical scavenging, reducing power, ferrous ion chelating and total antioxidant by phosphomolybdenum and -carotene bleaching methods), and report as well the enzyme inhibitory activities (against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), tyrosinase, α-glucosidase, and α-amylase), as well as the total phenolics, flavonoids, and condensed tannins. The reported results on Sideritis perfoliata highlight that methanol and water extracts generally show higher radical scavenging, and reducing power activities. A similar trend could be observed also for phosphomolybdenum and ferrous ion chelating activities. Only for -carotene bleaching assay, methanol extract shows lower activity.